2012
DOI: 10.1189/jlb.1111575
|View full text |Cite
|
Sign up to set email alerts
|

Sublytic concentrations of Staphylococcus aureus Panton-Valentine leukocidin alter human PMN gene expression and enhance bactericidal capacity

Abstract: CA-MRSA infections are often caused by strains encoding PVL, which can cause lysis of PMNs and other myeloid cells in vitro, a function considered widely as the primary means by which PVL might contribute to disease. However, at sublytic concentrations, PVL can function as a PMN agonist. To better understand this phenomenon, we investigated the ability of PVL to alter human PMN function. PMNs exposed to PVL had enhanced capacity to produce O(2)(-) in response to fMLF, but unlike priming by LPS, this response d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 54 publications
(72 reference statements)
5
66
0
Order By: Relevance
“…By virtue of binding C5aR, LukS-PV not only exerts its lytic activity on target host cells but also can facilitate the priming of primary human PMNs for activation by proinflammatory stimuli such as N-formyl-Met-Leu-Phe (fMLP). This finding fully supports previous studies that suggested that PVL could promote the proinflammatory responsiveness of PMNs when applied at sublytic concentrations (199,252,253).…”
Section: Leucocidin Cellular Receptors Dictate Cell and Species Specisupporting
confidence: 82%
See 1 more Smart Citation
“…By virtue of binding C5aR, LukS-PV not only exerts its lytic activity on target host cells but also can facilitate the priming of primary human PMNs for activation by proinflammatory stimuli such as N-formyl-Met-Leu-Phe (fMLP). This finding fully supports previous studies that suggested that PVL could promote the proinflammatory responsiveness of PMNs when applied at sublytic concentrations (199,252,253).…”
Section: Leucocidin Cellular Receptors Dictate Cell and Species Specisupporting
confidence: 82%
“…However, a substantial body of evidence now suggests that most, if not all, leucocidins have bona fide immune cell-activating properties and/or additional sublytic functions that occur in the absence of cell lysis (Fig. 6) (210,233,252,253,(264)(265)(266). Most studies evaluating the proinflammatory signaling properties of the leucocidins stem from work done with PVL and gamma-hemolysin (210,252,253,(264)(265)(266).…”
Section: Proinflammatory Receptor Engagementmentioning
confidence: 99%
“…A possible explanation is that LukAB may cause disease in the mouse through receptor-independent immunomodulatory mechanisms, as has been as shown for PVL. Similar to LukAB, PVL also displays cytolytic tropism toward human PMNs (16), but has been shown to elicit proinflammatory responses in human PMNs and macrophages (26,27) as well as murine PMNs and macrophages (35,36). These findings suggest that the roles of LukAB and PVL in the mouse may be better explained by immunomodulatory functions rather than cytolytic functions, and indicate that mouse models underestimate the true contribution of these toxins to S. aureus pathobiology in humans.…”
Section: Discussionmentioning
confidence: 73%
“…Despite the lack of overlap in cellular targets identified thus far, the staphylococcal leukotoxins have been shown to exhibit synergistic effects (26). The identification of CD11b as a cellular target for LukAB provides an explanation for the previously reported synergism between LukAB and PVL toward human PMNs (10,11), as sublytic concentrations of PVL increase CD11b surface levels on these cells (27). From an evolutionary standpoint, the use of multiple, nonoverlapping cellular targets provides an explanation for why S. aureus has such a large arsenal of cytotoxins and is such a welladapted pathogen when it comes to evading host PMNs.…”
Section: Discussionmentioning
confidence: 84%
“…At sublytic concentrations, LukAB and PVL alter cellular signaling by inflammasome activation, leading to IL-1β secretion (67,68), and PVL is capable of priming and activating human neutrophils, resulting in enhanced phagocytic function (69). In addition, toxin monomers appear to antagonize their receptors, which may interfere with phagocyte recruitment and function (61,62).…”
Section: Evasion and Manipulation Of Host Defensesmentioning
confidence: 99%